PENGUJIAN KANDUNGAN NUTRISI PAKAN BUATAN UTNUK IKAN IKAN LELE (Clarias Gariepinus) MELALUI UJI PROKSMAT - Petrus Yansen Seran; Yosy Gustasya; Regil Kentaurus Harryes (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Feed plays an important role in the success of African catfish (Clarias gariepinus) farming because it directly affects growth rate, fish health, and production efficiency. Therefore, nutritional content testing through proximate analysis is necessary to ensure the quality of the feed used. This study aimed to identify the nutrient content of formulated catfish feed and evaluate its compliance with the feed quality standards established in SNI 01-4087-2006. The research was conducted at the Nutrition and Feed Laboratory, Faculty of Animal Science, Marine Affairs, and Fisheries, at Nusa Cendana University. Proximate analysis was carried out on three feed formulations, namely P1, P2, and P3. The parameters analyzed included dry matter, crude protein, crude fat, crude fiber, ash content, carbohydrates, and nitrogen-free extract (NFE). Moisture content was determined using the oven-drying method, crude protein was analyzed using the Kjeldahl method, crude fat was measured using the Soxhlet extraction method, crude fiber was determined through acid and alkaline hydrolysis, and ash content was measured using the furnace method. The results showed that formulation P1 had the highest crude protein content at 36.371%, followed by P2 at 32.234% and P3 at 27.776%. The crude fat content of the three formulations was relatively similar, ranging from 13.367% to 13.620%, while crude fiber content ranged from 5.143% to 8.337%. The highest ash content was found in P1 at 17.699%, whereas the lowest was recorded in P3 at 14.968%. Based on the evaluation against SNI 01-4087-2006 standards, formulations P1 and P2 met the minimum crude protein requirement, while formulation P3 did not meet the specified standard. However, all tested feed formulations exhibited ash content exceeding the maximum allowable limit, indicating that improvements in raw material formulation are still required.